FRANCISCO DE ROJAS ZORRILLA Y AGUSTÍN MORETO. DOS EJEMPLOS DE TRATAMIENTO DE LA MITOLOGÍA - Estefanía Álvarez, Dulce (Myrtia, 2001)
The aim of this paper is to study the treatment of the mythological topic of Progne and Filomela in the works of two Spanish playwrights, Rojas Zorrilla’s Progne y Filomela and Agustín Moreto’s El desdén con el desdén.